Extraction and characterization of cellulose nanocrystals from tea leaves waste fibers - Abdul Rahman, Nur Hayati; Chieng, Buong Woei; Ibrahim, Nor Azowa; Abdul Rahman, Norizah (MDPI, 2017)
The aim was to explore the utilization of tea leaf waste fibers (TLWF) as a source for the production of cellulose nanocrystals (CNC). TLWF was first treated with alkaline, followed by bleaching before being hydrolyzed with concentrated sulfuric acid. The materials attained after each step of chemical treatments were characterized and their chemical compositions were studied. The structure analysis was examined by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). From FTIR analysis, two peaks at 1716 and 1207 cm−1—which represent C=O stretching and C–O stretching, respectively—disappeared in the spectra after the alkaline and bleaching treatments indicated that hemicellulose and lignin were almost entirely discarded from the fiber. The surface morphology of TLWF before and after chemical treatments was investigated by scanning electron microscopy (SEM) while the dimension of CNC was determined by transmission electron microscopy (TEM). The extraction of CNC increased the surface roughness and the crystallinity index of fiber from 41.5% to 83.1%. Morphological characterization from TEM revealed the appearance of needle-like shaped CNCs with average diameter of 7.97 nm. The promising results from all the analyses justify TLWF as a principal source of natural materials which can produce CNC.